(untitled) (Journal of the College of Basic Education, 2022)
The experiences that students go through and what they contain of emotions, emotions and feelings can affect their way of thinking, as they interpret things without an objective view, which leads them to dire results that affect their achievement and academic level, so they fail to rely on themselves in the search for information, reading and curiosity. , especially in our current era, which has witnessed a wide diversity in the various technological means of communication, as they lose confidence in themselves and rely on other sources to acquire learning, and they have what is called (cognitive dependence), which indicates a latent behavioral readiness in childhood and may appear at the end of the adolescence stage. Or the stage of adulthood, and gives it a characteristic of relative stability in the later stages of life (Youssef, 2011: 85). Cognitive dependency is characterized by the difficulty of making decisions without relying on others and assigning responsibility to others in most areas of an individual’s life and his inability to object to others for fear of losing their support for him and facing the difficulty of starting any project or work that depends on his own capabilities and annoyance with loneliness with attachment to others and research Eagerly about personal relationships that are very resourceful and helpful, and unrealistically preoccupied with the fear that others will leave him to take on his responsibilities (Ibrahim, 2005: 105). Therefore, the research problem arises in the following question (What is the level of cognitive dependency among the students of the kindergarten department?)